2018
DOI: 10.1051/e3sconf/20186704035
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of cellulose acetate from palm oil bunches and dried jackfruit leaves

Abstract: Cellulose acetate is a natural polymer, that is widely used in various industries, especially fiber and plastics. Cellulose acetate was created by an esterification reaction of cellulose and acetic anhydride. The raw materials used in this research were empty fruit bunches of palm oil and dried jackfruit leaves, because utilization of waste, available in large quantities, and contain high cellulose. The objective of this study was to obtain high yield cellulose and cellulose acetate from palm oil bunches and j… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 2 publications
0
7
0
Order By: Relevance
“…The activation of cellulose using acetic acid before undergoing acetylation reaction is highly dependent on the amount of acetic acid used. It helps to trigger the expansion of the cellulose structure resulting in higher surface area and breakage of cellulose bonding (Tristantini and Sandra 2018). The formation of particle of CA increased in both size and number in increasing acetic acid.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The activation of cellulose using acetic acid before undergoing acetylation reaction is highly dependent on the amount of acetic acid used. It helps to trigger the expansion of the cellulose structure resulting in higher surface area and breakage of cellulose bonding (Tristantini and Sandra 2018). The formation of particle of CA increased in both size and number in increasing acetic acid.…”
Section: Resultsmentioning
confidence: 99%
“…Cellulose is activated when mixing with acetic acid, then the mixture is further acetylated with acetic anhydride with the presence of sulfuric acid as a catalyst. Activation of cellulose with acetic acid expands the cellulose structure which increases the reactive surface area and weakens the intermolecular hydrogen and hydroxyl bond of the cellulose (Tristantini et al 2018). This subsequently facilitates the binding of cellulose with the acetyl group from acetic anhydride during the acetylation process of CA formation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lignin must be removed, to obtain cellulose with high purity through the delignification process. 20 The delignification process can be carried out using physical, chemical, physicochemical and biological methods. 21 Biological or enzymatic methods cannot be applied directly to lignocellulosic raw materials because lignin inhibits the penetration of fungi or enzymes into the cell walls of the lignocellulosic material.…”
Section: Introductionmentioning
confidence: 99%
“…The green synthesis approach, exploiting plant extracts as reducing agents, offer cost—and eco-friendly alternatives to the physical and chemical methods of synthesis. Several studies have reported the synthesis of cellulose using jackfruit leaves [ 8 ], Retama raetam [ 9 ] and Citrullus lanatus [ 10 ] as capping agent. In this present study, cellulose was synthesized from Sesamum indicum , an oilseed crop cultivated in Nigeria.…”
Section: Introductionmentioning
confidence: 99%